G20(P) Typhlitis in children receiving chemotherapy. (27th April 2016) - Bamber, M; Platt, K; Park, K; Chakraborty, S; Grant, H; Lakhoo, K; Wilson, S; Wheeler, K; Hall, G; Qureshi, A; Bhatnagar, N
Abstract : Background and aims: Children receiving chemotherapy are at an increased risk of typhlitis, also known as neutropenic enterocolitis. It is characterised by fever and abdominal pain in a neutropenic patient receiving chemotherapy. It is a significant cause of mortality and morbidity in paediatric haemato-oncology patients. We review our experience with typhlitis in children with cancer over the past 5 years. Most cases can be managed conservatively but one case importantly highlights the rare need for surgical intervention. Methods: A retrospective analysis of case notes was performed of all paediatric haemato-oncology patients with typhlitis at a tertiary paediatric hospital from January 2011 till present. Results: We report 6 cases of typhlitis at our institution over the last 5 years. 3 patients had acute lymphoblastic leukaemia (ALL), one had haemophagocytic lymphohistiocytosis (HLH), one had relapsed Wilm's tumour and one had neuroblastoma. 3 were male; 3 were female. Median age at diagnosis was 12 years (range 5–16 years). All 6 cases had presented with abdominal pain, neutropenia and fever. Neutrophil count ranged from zero to 0.67 × 10 9 /l. Radiological investigation by US/CT showed bowel wall thickening in all 6 cases in keeping with typhlitis. All patients initially received conservative medical management with bowel rest, intravenous nutritional support, broad spectrum intravenous antibiotics and sometimes G-CSF support. PICU support was needed for some these patients (both inotropic support and ventilation). All patients improved with neutrophil recovery but one patient had prolonged neutropenia and required definitive surgical management and hemicolectomy. Conclusion: Typhlitis is a life-threatening complication in paediatric haemato-oncology patients particularly those receiving intensive chemotherapy with corticosteroid exposure and prolonged periods of neutropenia. Most cases can be managed conservatively however surgical intervention may be required in few cases that fail aggressive medical management or develop complications such as perforation. Increased clinical awareness of typhlitis is necessary to establish an early diagnosis. Radiological investigation with US/CT is essential to make a definitive diagnosis. Early surgical opinion is required for appropriate management.